Molecular Identification of HIV-1 in the Presence of Hepatitis B Virus and Hepatitis C Virus Co-infections - Sayan, Murat; Ozguler, Muge; Yildirim, Figen Sarigul; Yildirmak, Taner; Gunduz, Alper; Dokuzoguz, Basak; Unal, Serhat (Galenos Publ House, 2020)
Background: Because of their similar modes of transmission, the simultaneous infection of viral hepatitis and human immunodeficiency virus are increasingly seen as a big problem related to human health. Aims: To determine the drug mutations in hepatitis B virus and/or hepatitis C virus co-infected human immunodeficiency virus-1 patients in Turkey. Study Design: Retrospective cross-sectional study. Methods: The present study was conducted between 2010 and 2017. HBsAg, anti-hepatitis C virus, and anti-human immunodeficiency vim were tested with ELISA. All anti-human immunodeficiency virus positive results by ELISA were verified for anti-human immunodeficiency virus positivity by a Western blot test, and Antihuman immunodeficiency virus positive patients with HBsAg andior anti-hepatitis C virus positivity were included in the study. Subtyping and genotypic resistance analyses were performed by population sequencing of the viral protease and reverse transcriptase regions of the human immunodeficiency virus-1 pol gene. Results: We detected 3896 human immunodeficiency virus-1 positive patients whose sera were sent from numerous hospitals across the country to our polymerase chain reaction unit for detection of drug resistance mutations and whose molecular laboratory tests were completed. Viral hepatitis co-infections were detected in 4.3% (n=170) of patients. Hepatitis B virus and hepatitis C virus co-infection were observed in 3.2% and 0.5% of all human immunodeficiency virus-I infected patients, respectively. The major human immunodeficiency virus-1 subtype detected was group M, subtype B (62.9%). However, 13.5% of drug resistance mutation motifs were found in human immunodeficiency virus-1 genomes of patients included in the study. Conclusion: Due to similar transmission routes, HIV1 patients are at risk of hepatitis B and C virus co-infection. However, antiretroviral drug resistance mutation model is similar to patients with hepatitis negative.
19th Annual Meeting of the European-Society-for-Clinical-Virology -- SEP 14-17, 2016 -- Lisbon, PORTUGAL
Keywords: Co-infection; hepatitis B virus; hepatitis C virus; HIV-1; molecular epidemiology